Numerical Simulation and Validation of Ozone Concentration Profile in Green Gram (Vigna radiate) Bulks. (2nd January 2017) - Pandiselvam, R.; Kothakota, Anjineyulu; Thirupathi, V.; Anandakumar, S.; Krishnakumar, P.
ABSTRACT: The new fumigant ozone offers an alternative to contact insecticides such as phosphine and methyl bromide as a grain fumigant. This study was carried out to test the flow characteristics of ozone from points of release to the available concentration of ozone to kill pests at other areas along the storage bin. A mass transfer model which predicts ozone concentration as a function of time was applied along with continuity equation to simulate the ozone transfer in a storage bin. Ozone exchange rate based on grain bed thickness was taken into account and evaluated using the correlation developed during the experiment. The relative error between the experimental and predicted ozone concentration values for the entire bin geometry was less than 25.7%. Overall, the general trends of measured ozone concentration were compatible with the simulated ones.